Trabajo decente desde los lineamientos de la OIT: aplicabilidad en el sector agrícola cebollero de Aquitania Boyacá (2020)
The concept of "decent work" is an essential element in the legal systems of democratic States and even more so of those that are part of the International Labour Organization (ILO). Likewise, the obligation of the Member States to guarantee labour rights in the context of decent work must be reflected in effective action to protect it even more in the agricultural sector. From this logic, the proposed objective leads to an analysis of "decent work from the guidelines of the ILO and its applicability in the agricultural sector of the municipality of Aquitaine- Boyacá". Research developed from a qualitative approach, which allowed interaction with the population sample. Likewise, it was necessary to choose 46 workers from the agricultural sector, in 5 companies marketing long onions, each with an average of 13 workers, in which a semi-structured interview was carried out, establishing categories and subcategories that allowed the information to be specified, in addition to the analysis and interpretation of both primary and secondary sources that were taken into account for this purpose. The result of this process has allowed us to infer that workers in the agricultural sector suffer from the protection of the State in labor matters, and even less from the guarantee that the convention with the ILO provides in order to achieve decent work. Therefore, it is important to rethink and restructure the normative methodology regarding its application in order to guarantee labor rights to this population.